Pengaruh Lama Pengecambahan terhadap Kandungan -Tokoferol dan Senyawa Proksimat Kecambah Kacang Hijau (Phaseolus radiatus L.) - Sri Anggrahini (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2007)
The objective of the research was to study the effect of germinating time on the a-tocopherol production and the change of lipid, protein, ash, and carbohydrate contents of the mung bean sprout. The germination was conducted during 0, 12, 24, 36 and 48 hours. The result showed that a-tocopherol were produced on the mung bean sprout after 36 hours and 48 hours incubation and a-tocopherol content were 0,21 µg/g and 0,53 mg/g mung bean sprout, respectively. Protein, ash and carbohydrate contents did not show significant change, but water and lipid contents showed significant change during germination time.ABSTRAKTujuan penelitian adalah mengetahui pengaruh lama perkecambahan terhadap produksi a-tokoferol dan perubahan kandungan lemak, protein, abu dan karbohidrat kecambah kacang hijau. Proses perkecambahan dilakukan selama 0, 12, 24, 36 dan 48 jam. Hasil penelitian menunjukkan bahwa a-tokoferol diproduksi waktu inkubasi selama 36 dan 48 jam dengan kandungan a-tokoferol masing-masing 0,21 μg/g kecambah kacang hijau dan 0,53 μg/g kecambah kacang hijau. Kandungan protein, abu dan karbohidrat tidak berubah secara nyata selama proses perkecambahan, tetapi kandungan air dan lemak berubah secara nyata.